The Effect of Different Seed Densities on Some Hybrid Maize (Zea mays L.) Type’s Yield in Eskişehir Conditions - Kutalmış TURHAL (Trakya University Journal of Natural Sciences, 2016)
In this study, the effects of different plant spacing of some commercial maize varieties on agricultural features were investigated in Eskişehir, forming the western transitional zone of Central Anatolia. ADA_9510, ADA_9516, TTM_815 and BC_6661 were used as the varieties while the plants were applied as “70×20”, “70×15”, “60×20”, “60×25” and “50×30”cm. In trials performed in Eskişehir conditions, plantation was performed according to split plots in Randomized Complete Blocks with 4 replications, irrigation was performed with microirrigation and fertilizer application was performed as fertilization. The results showed that yield and yield factors could vary according to the maize variety and plantation density. In the present oneyear study, “60×25”cm and “50×30”cm density appeared to become the prominent spacing value.